1972
DOI: 10.1063/1.1661157
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Radiation Damage in Epitaxial Gallium Arsenide

Abstract: Electrical and photoluminescence measurements were carried out on liquid epitaxial GaAs single crystals after irradiation at room temperature by 1.25-MeV 60Co γ rays. Following each of a series of irradiations, Hall measurements were made on both n- and p-type crystals as a function of temperature between 77 and 300°K. The n-type crystals exhibited energy levels 0.13, 0.16, and 0.30 eV below the conduction band minimum after irradiation. The 0.13- and 0.16-eV levels were introduced during irradiation at roughl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It is well known that irradiation of high-energy particles, such as neutrons and electrons, can induce structural defects in semiconductors. In the past few decades, there were many reports discussing the irradiation-induced defects in silicon, 7 GaAs, [8][9][10] GaP, 11 and InP. 12 However, only a few studies 13,14 have been reported on the effects of neutron irradiation on the microstructural and optical properties of GaN thin films.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that irradiation of high-energy particles, such as neutrons and electrons, can induce structural defects in semiconductors. In the past few decades, there were many reports discussing the irradiation-induced defects in silicon, 7 GaAs, [8][9][10] GaP, 11 and InP. 12 However, only a few studies 13,14 have been reported on the effects of neutron irradiation on the microstructural and optical properties of GaN thin films.…”
mentioning
confidence: 99%
“…19 Usually, carrier removal is mainly due to the trapping of majority carriers by structural defects. 8,9,21,22 To test this idea and to investigate the crystal structure of the irradiated GaN, PL spectra of the samples were taken. Figure 2 shows the low-temperature PL spectra of the samples.…”
mentioning
confidence: 99%
“…Several studies on the annealing of radiation-induced defects in GaAs have shown the changes in the electrical properties of the material are due to the introduction of those defects [10][11][12][13][14]. Aukerman et al [10] showed the recovery of electron-induced defects in p-type GaAs samples to be qualitatively different from that in n-type GaAs samples.…”
Section: Introductionmentioning
confidence: 97%
“…Usually, carrier removal is mainly due to the trapping of majority carriers by structural defects [8,9,20,21]. To test this idea and to investigate the crystal structure of the irradiated GaN, XRD scans of the samples were made.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that irradiation by high-energy particles such as neutrons and electrons can induce structural defects in semiconductors. In the past few decades, there have been many reports discussing the irradiation-induced defects in silicon [7], GaAs [8][9][10], GaP [11] and InP [12]. However, only a few studies [13,14] have reported on the effects of neutron irradiation on the microstructural and optical properties of GaN thin films.…”
Section: Introductionmentioning
confidence: 99%